An integrated parameter calibration method and sensitivity analysis of microparameters on mechanical behavior of transversely isotropic rocks. (February 2022) - Xu, Zhenhao; Wang, Zhaoyang; Wang, Wenyang; Lin, Peng; Wu, Jie
Abstract: The calibration of dual-models in particle flow code (PFC) is an open research challenge because of the complexity and dependence of microparameters in each model. Aiming at addressing this challenge, an integrated parameter calibration method based on linear parallel bonding model (LPBM) and smooth joint model (SJM) (CM-LPBM&SJM) was developed in the present work and applied to transversely isotropic rocks. A calibration parameter index system was first proposed. Numerical simulations were conducted to obtain the relationship between macroparameters and microparameters. Subsequently, an LPBM and SJM parameter calibration priority was established by linking microparameters of each model. A macro–micro parameter functional representation system was then developed. In addition, iteration corrections were conducted to improve calibration accuracy. Finally, a set of standardized microparameter calibration procedures for transversely isotropic rocks was proposed. CM-LPBM&SJM solved the challenge of the complexity and dependence of microparameters by establishing microparameter calibration priority. To further verify the feasibility of the proposed method, a case study was conducted, and the error was found to be less than 4%. Hence, CM-LPBM&SJM introduces a new perspective for dual-model parameter calibration.